2005
DOI: 10.1111/j.1523-5378.2005.00293.x
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal CpG‐Oligodeoxynucleotide is a Potent Adjuvant of Vaccine against Helicobacter pylori, and T Helper 1 Type Response and Interferon‐γ Correlate with the Protection

Abstract: CpG-ODN given intranasally is a potent adjuvant for development of a H. pylori vaccine. Th1-type response and IFN-gamma are involved in the protection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
2
4

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 36 publications
(54 reference statements)
3
33
2
4
Order By: Relevance
“…A previous study by Shi et al reported protection against H. pylori challenge using whole cell sonicate and CpG sequences [14]. Protection was associated with high levels of IgG2a and IFN-γ and was abrogated in IFN-γ knockout mice, which is in agreement with our results and emphasizes the importance of Th1 immunity for protection against H. pylori.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…A previous study by Shi et al reported protection against H. pylori challenge using whole cell sonicate and CpG sequences [14]. Protection was associated with high levels of IgG2a and IFN-γ and was abrogated in IFN-γ knockout mice, which is in agreement with our results and emphasizes the importance of Th1 immunity for protection against H. pylori.…”
Section: Discussionsupporting
confidence: 83%
“…However, the LPS+/ CpG immunized mice were significantly more protected from challenge when compared to mock controls. Although the magnitude of this effect was modest, it was within the range of that seen in some other studies of H. pylori immunization [14,31,32].…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Lisados o sonicados de H. pylori, en conjunción con adyuvantes como TC, fueron capaces de provocar disminuciones significativas en la carga bacteriana 14 . Algunos grupos reportaron un efecto significativo en dicha reducción, asociado a la ruta de vacunación y al adyuvante empleado, siendo utilizada preferentemente la aplicación intranasal de los antígenos crudos 15,16 . La reciente utilización de los oligodesoxirribonucleótidos CpG como adyuvantes para evitar el efecto tóxico asociado a TC en humanos, ha sido evaluada por numerosos grupos observándo-se reducción significativa en la carga bacteriana 16,17 .…”
Section: Factibilidad De Una Vacuna: Modelos Animalesunclassified